2002
DOI: 10.1113/eph8702432
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Primary Thoracic Blast Injury and Morphine on the Response to Haemorrhage in the Anaesthetised Rat

Abstract: Primary thoracic blast injury causes a triad of bradycardia, hypotension and apnoea mediated in part via a vagal reflex. Blast casualties may also suffer blood loss, and the response to progressive simple haemorrhage is biphasic: an initial tachycardia followed by a vagally mediated reflex bradycardia which can be attenuated by μ opioid agonists. The aims of this study were to determine the effects of thoracic blast injury on the response to subsequent haemorrhage, and the effects of morphine, administered aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…A transient bradycardia (as observed in Figure 1) is frequently reportedly in PBLI and is due to a vagal nerve mediated reflex, which in the absence of further insult resolves rapidly 7,8 . We saw a modest but sustained increase in respiratory rate after PBLI, which may have been compensatory as a result of pulmonary damage and reduced gasexchange, thereby maintaining peripheral oxygenation in subjects 33 throughout the study period.…”
Section: Modelmentioning
confidence: 81%
See 1 more Smart Citation
“…A transient bradycardia (as observed in Figure 1) is frequently reportedly in PBLI and is due to a vagal nerve mediated reflex, which in the absence of further insult resolves rapidly 7,8 . We saw a modest but sustained increase in respiratory rate after PBLI, which may have been compensatory as a result of pulmonary damage and reduced gasexchange, thereby maintaining peripheral oxygenation in subjects 33 throughout the study period.…”
Section: Modelmentioning
confidence: 81%
“…Studies investigating the subsequent immune response have been reported most commonly in rats [5][6][7][8][9][10] , mice [11][12][13][14][15] and swine 16,17 . These studies have offered overwhelming evidence of the neutrophil response to PBLI in animal models, with increases in circulating and broncho-alveolar lavage fluid (BALF) neutrophils, increases in Myeloperoxidase (MPO) activity in the lung, and neutrophil staining by histology [9][10][11][12]14,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Bias was likely to arise between blast and non-blast injured groups because haemorrhage after blast results in more rapid early falls in arterial blood pressure [53], resulting in greater uncontrolled blood loss from those subjected to haemorrhage without blast injury. The problem was solved by incorporating an initial phase of controlled haemorrhage (30% total estimated BV), at the conclusion of which arterial blood pressure had diminished to similar levels regardless of prior blast exposure.…”
Section: Potential Models Of Haemorrhage Relevant To Battlefield Casumentioning
confidence: 99%
“…In civilian mass casualty situations, such as terrorist bombings in confined spaces, there is often disruption to infrastructure and security issues relating to secondary devices that can result in delayed evacuation. Furthermore, the response to hemorrhage can be modified significantly by concomitant injuries, 14,15 and consequently the effectiveness of resuscitation strategies may be influenced by the response to the injuries. Therefore, although permissive hypotension is a widely adopted strategy in trauma resuscitation, the success of this approach requires a full investigation and understanding of the mechanisms of injury and their physiological consequences.…”
mentioning
confidence: 99%